2013
DOI: 10.15230/scsk.2013.39.4.303
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Anti-inflammatory Activities of Fermented Scutellaria baicalensis Extracts using Lactobacillus rhamnosus

Abstract: This study was performed to investigate the anti-inflammatory activities of fermented Scutellaria baicalensis extracts using Lactobacillus rhamnosus. The extracts were WE (water extract at 100 ℃ for 24 h), EE (70% ethanol extract at 60 ℃ for 24 h), FWE (fermented and water extract at 60 ℃ for 24 h), FEE (fermented and 70% ethanol extract at 60 ℃ for 24 h). The cytotoxicity of the extracts was in the range of 11.2 ∼ 15.6 % at 1.0 mg/mL concentratioin. The FEE showed the lowest activity at 1.0 mg/mL concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…The main active components in this plant are flavonoids, which are known for their free radical-scavenging activity [7]. In a previous study, it was stated that these compounds exhibit strong antioxidant properties, efficiently inhibiting the production of reactive oxygen species (ROS) during oxidative processes, as well as demonstrating anti-bacterial, anti-allergen, anti-inflammatory, anti-hypertensive, and antiviral activities [8]. Remarkably, S. baicalensis has shown anti-cancer activity by hindering prostaglandin E2 (PGE2) production [9].…”
Section: Introductionmentioning
confidence: 99%
“…The main active components in this plant are flavonoids, which are known for their free radical-scavenging activity [7]. In a previous study, it was stated that these compounds exhibit strong antioxidant properties, efficiently inhibiting the production of reactive oxygen species (ROS) during oxidative processes, as well as demonstrating anti-bacterial, anti-allergen, anti-inflammatory, anti-hypertensive, and antiviral activities [8]. Remarkably, S. baicalensis has shown anti-cancer activity by hindering prostaglandin E2 (PGE2) production [9].…”
Section: Introductionmentioning
confidence: 99%
“…Among natural product extraction methods, it has been reported that lactic acid bacteria used in the fermentation process have various effects such as immunity enhancement, cancer prevention effect, and antioxidant effect. It is possible to maximize the yield of active ingredients and physiologically active components by the effect, and new components can be expected (Choi et al 2013;Kong et al 2008). In particular, the lactic acid bacteria fermentation process is more efficient than other process methods as it requires less fermentation time and less cost for the process (Ryu and Kwon 2012).…”
Section: Introductionmentioning
confidence: 99%
“…그러나 해조류에 포함되어 있는 탄수화물의 대부분이 비소화성 복합다당류로서 이러한 기존 추출 방법으로는 유 용성분을 다량 추출해 내는데 한계점이 있다 [10]. 이러한 단 점을 극복하기 위한 방법으로 효소처리법과 유용 미생물을 이용한 발효법으로 유용성분을 추출하고자 하는 시도가 행 해지고 있다 [9,[11][12][13]. 특히, 발효는 미생물의 대사활동에 의 해 유용성분의 추출 효율성을 극대화 시키는 동시에 다양한 효능을 가지는 물질을 생성할 수 있는 것으로 알려져 있다 [11].…”
Section: Introductionunclassified
“…이러한 단 점을 극복하기 위한 방법으로 효소처리법과 유용 미생물을 이용한 발효법으로 유용성분을 추출하고자 하는 시도가 행 해지고 있다 [9,[11][12][13]. 특히, 발효는 미생물의 대사활동에 의 해 유용성분의 추출 효율성을 극대화 시키는 동시에 다양한 효능을 가지는 물질을 생성할 수 있는 것으로 알려져 있다 [11]. Lactobacillus casei는 주로 치즈 생산에 이용되는 유산 균으로 탄수화물을 분해시키는 효소인 아밀라아제 (amylase) 를 생산하며 다당 성분의 처리에 의해 기능성 해조 올리고당 이 생성된다고 알려져 있어 탄소원으로 포도당을 첨가하여 유용성분의 추출률을 높이는데 이용되고 있다 [9].…”
Section: Introductionunclassified